A rectangular inset-fed patch antenna with defected ground structure for ISM band - Islam, Md. Shazzadul; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Hossain, A. K. M. Zakir (IEEE Explore, 2018)
An operating center frequency of 2.45 GHz rectangular inset fed microstrip patch antenna with defected ground structures for ISM band applications has been presented in this paper. The return loss of the proposed antenna is -29.726 dB with impedance bandwidth for $S_{11}< _{-}10dB$ is 2.441 to 2.462 GHz, that covers IEEE S02.11 g/n OFDM 20 MHz channel width. The antenna has a directional far-field pattern at the boresight direction of $0^{o}$ with a good total antenna efficiency of -1.39 dB. The proposed antenna is light weighted, easy to fabricate and achieved good directivity gain of 7.04 dBi and VSWR of 1.06 at the resonant frequency that makes it suitable for WLAN applications.